VALUES ORIENTATION AND LEARNING BEHAVIOR OF GRADE 12 LEARNERS IN THE DISTRICT OF TAPAZ WEST - Gabeja, Krislyn Panes (President University, 2025)
The study aimed to determine the degree of values orientation and level of learning behavior of three hundred eighty-five (385) Grade 12 students in the District of Tapaz West for school year 2023-2024. Statistical tools used to analyze and interpret data were frequency count, percentage, mean, t-test, analysis of variance and Pearson r. The findings of the study revealed that Grade 12 learners have high degree of values orientation as a whole, very high degree of personal values orientation and high degree of social values orientation. On the other hand, the level of learning behavior as a whole was for both curricular and extra-curricular engagement. There was no significant difference in scores the degree of values orientation as a whole of the respondents when classified according to their profile. There was no significant difference in the level of learning behavior of the respondents when classified according to their socio-demographic profile. There was a highly significant, strong positive correlation between the degree of values orientation and the level of learning behavior in both curricular and extra-curricular activities. It validates the values orientation and learning behavior of grade 12 students of Tapaz West District correlated with each other and relationship is highly significant. The research provides a clear view that the more the learners have strong and consistent values, the more they are likely to be involved and motivated in their learning activities. Thus, teachers and parents must support students’ positive lifelong learning outcomes and promote a more equitable and just society.